Resentment and Admiration: Public Opinion Toward Teachers and Public Sector Employees in Ontario - Erl, Chris; McGregor, R. Michael; Lucas, Jack; Anderson, Cameron D. (Canadian Journal of Education / Revue canadienne de l'éducation, 2023)
Public opinion toward teachers and other public sector workers is an important factor in Ontario provincial politics. This article uses public opinion data to measure, and identify the correlates of, resentment and admiration of these groups, and to identify the relationship between these attitudes and support for political parties in Ontario. Survey data from over 4,000 Ontarians, collected at the time of the 2022 provincial election, show that Ontarians have greater admiration for, and less resentment toward, teachers than toward other provincial government workers. The data also reveal several factors related to these attitudes, including comparative assessments of compensation and workload, and relationships with members of these groups. Finally, the data show that attitudes toward teachers, but not other public sector workers, are related to provincial vote choice, with negative attitudes toward teachers predicting PC Party support. Teachers are clearly a more salient “target” of resentment in Ontario provincial politics. These findings have implications for educational policy and the tactics of teacher unions.